Appointment of Guardian Hakim for Pregnant Couples Outside of Marriage Perspective of Islamic Law: Case Study at KUA Mojo District, Kediri Regency - Moh. Abu Muhni Rizkon; Ahmad Badi (Legitima : Jurnal Hukum Keluarga Islam, 2021)
The position of the guardian is very important in a marriage contract and the person entitled to be the guardian is the nasab guardian, this is stated in KHI articles 19-22. However, in reality there are factors that cause the nasab guardian to be absent or reluctant to marry off his daughter. This factor is pregnancy outside of marriage, this is certainly a disgrace to the family. In this case, so that the marriage can continue, the scholars allow the use of a judge's guardian, of course, with certain conditions. this research was conducted at the KUA Mojo District, Kediri Regency. This research uses a qualitative method, namely by observing the phenomenon of the use of wali hakim against Married By Accident couples at the KUA Mojo District, Kediri Regency and then the data obtained is presented with descriptive methods. Based on the results of the study, it can be concluded that the implementation of Islamic rules on the judge's guardian of the married by accident couple is legal (valid). This is in view of the mudhorot side that is so great if not married, the child after birth will have a psychological burden because it does not have a father, the family will bear the moral burden for life.